Association of single nucleotide polymorphisms in the first intron of the Fat mass and obesity associated (FTO) gene with obesity risk in Asians: a meta-analysis - Mohammadi, Hamed; Shab-Bidar, Sakineh; Kazemi, Fatemeh; Sadeghi, Alireza; Speakman, John R.; Djafarian, Kurosh (Progress in Nutrition, 2019)
Objective: This meta-analysis was performed to examine the association between the fat mass and obesity associated (FTO) gene polymorphisms and the risk of obesity in Asian populations. Methods: We conducted a meta-analysis based on searches of PubMed and Scopus up to October 19th, 2015 to identify relevant studies. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using random- or fixed-effect models. Results: Fourteen studies for rs9939609 (8810 cases and 17031 controls) and eight studies for rs8050136 (3305 cases and 6841 controls) were finally included. There was a significant association between both polymorphisms and the risk of obesity under all models. For rs9939609, allele model (A allele vs. T allele): OR=1.29, 95%CI 1.20–1.39; recessive model (AA vs. TT+TA): 1.45, 95%CI 1.26-1.65; dominant model (AA+TA vs. TT): OR=1.31, 95 %CI 1.19-1.44; and the homozygous model (AA vs. TT): OR=1.63, 95%CI 1.39–1.87. For rs8050136, allele model (A allele vs. T allele): OR=1.32, 95%CI 1.16–1.48; recessive model (AA vs. TT+TA): 1.36, 95%CI 1.09-1.62; dominant model (AA+TA vs. TT): OR=1.36, 95%CI 1.16-1.56; and the homozygous model (AA vs. TT): OR=1.51, 95%CI 1.20–1.82. Conclusions: This meta-analysis indicated a significant positive association between the single nucleotide polymorphisms near to FTO (rs9939609 and rs8050136) and obesity risk among Asians.